ANALISIS HUBUNGAN KUALITAS PRODUK, HARGA, DAN WORD OF MOUTH (WOM) TERHADAP KEPUTUSAN PEMBELIAN PADA DEPOT TOMMY KEDIRI - Aldyawan, Aling; Soedjoko, Dodi Kusuma Hadi (Universitas Nusantara PGRI Kediri, 2021)
This review aims to review product quality, price and word of mouth on purchasing decisions at Tommy Kediri Depot. In this review, the population is Depot Tommy consumers who have come for the last two months and do not make repeat purchases. Sampling was based on the Rao Purba formula and the results obtained were 97 respondents. Data collection techniques used were observation, interviews, and distributing questionnaires. Sampling using the accidental sampling method, that is, someone incidentally meets the eye of the reviewer, is used as a sample. The results of the statistical data review, the indicators in this review are Valid and Reliable. The results of the review show that product quality, price and Word of Mouth either partially or simultaneously are significant to purchasing decisions. Keywords: product quality, price, word of mouth, purchasing decisions.